Characterization of All Carbon Composites Reinforced with In situ Synthesized Carbon Nanostructures. Issue 1611 (2014) - Hernandez, F. C. Robles; Calderon, H. A.; Barber, D.; Okonkwo, A.; Olivares, R. Ordoñez; Hadjiev, V.
ABSTRACT: In this work results are presented regarding carbon composites produced by high energy mechanical milling and consolidated by spark plasma sintering. The involved energy input in such a processing method has been used to develop composite materials and to synthesize effective in-situ reinforcement. In the as milled and sintered composites various dispersions of graphene, graphitic carbon, and diamonds in an amorphous matrix are found. The graphene, graphitic carbon and diamond phases are synthesized primarily during milling. The TEAM-05 microscope has been used for characterization that is complemented with Raman results. The spark plasma sintering method enhances the presence of graphene, graphitic carbon and diamonds.